Driving Sales by Shopee Live: Investigating the Determinants of Impulsive Purchase Behavior - Putri Linggasari Sofi; Jati Waskito (Journal of Consumer Sciences, 2026)
Background: Digital technology has transformed customer buying behavior, particularly through live-streaming commerce. Interactive features enable real-time engagement between sellers and consumers, making purchasing more dynamic and time-sensitive. Purpose: This study investigates drivers of impulsive buying on Shopee Live using the Stimulus–Organism–Response (S–O–R) framework. It examines how five external stimuli, namely the social presence of streamers, viewers, and products, promotional incentives, and product scarcity, influence consumers’ internal states (perceived risk and perceived value), which in turn affect their urge to buy impulsively. Method: A quantitative approach with purposive sampling targeted individuals who had made purchases via Shopee Live. Data from 178 respondents were collected through surveys and analyzed using PLS-SEM. Findings: The social presence of streamers, viewers, and products substantially reduces perceived risk. However, only product social presence and promotional information significantly enhance perceived value. Both perceived risk and value substantially influence the urge to buy impulsively, with perceived risk exerting a negative effect and perceived value a positive one. Conclusions: Perceived risk and perceived value mediate the relationship among external stimuli and impulsive buying. The distinct effects of social presence and promotional strategies highlight the importance of targeted marketing in live-streaming commerce. Research implication: The findings emphasize optimizing interactive, product-focused content while ensuring transparent promotional communication. Managing consumers’ perceptions of risk and value can strengthen engagement and drive sales performance on live-streaming platforms.